The Contribution of Immanuel Kant’s Criticism to the Development of Modern Philosophy of Science - Rendy Shaputra; Ramsiah Tasruddin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Immanuel Kant’s critical philosophy represents an important turning point in the development of modern philosophy of science, as it offers a middle position between rationalism and empiricism. Rationalism places reason as the primary source of knowledge, while empiricism emphasizes sensory experience as the basis for the formation of knowledge. Through critical philosophy, Kant argues that knowledge does not originate solely from pure reason or experience, but is formed through a synthesis between a priori structures of the mind and empirical data obtained through experience. This study employs a qualitative method with a library research approach by examining books, scholarly journals, and academic literature relevant to Kant’s thought. The data are analyzed using a descriptive-interpretative method to understand the concept of critical philosophy and its relevance to modern philosophy of science. The findings indicate that Kant’s critical philosophy provides an epistemological foundation for modern science, particularly in terms of rational judgment, verification, critical reflection, and the examination of knowledge claims. Therefore, Kant’s thought contributes to the development of a scientific paradigm that is systematic, objective, critical, and open to the advancement of new knowledge.